Imports Under a Foreign Exchange Constraint : The Case of the Islamic Republic of Iran - Mazarei, Adnan (Washington, D.C. : International Monetary Fund, 1995)
This paper examines the role of foreign exchange receipts in determining Iran's imports during 1961/62-1992/93. It provides evidence of the existence of long-term relationship between imports and foreign exchange receipts, as well as the traditional price and output variables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet